Surveillance of transmitted drug resistance to integrase inhibitors in Spain: implications for clinical practice. (5th March 2019) - Alvarez, Marta; Casas, Paz; de Salazar, Adolfo; Chueca, Natalia; Guerrero-Beltran, Carlos; Rodríguez, Carmen; Imaz, Arkaitz; Espinosa, Nuria; García-Bujalance, Silvia; Pérez-Elías, María Jesús; García-Alvarez, Mónica; Iribarren, Jose Antonio; et al.
Abstract: Background: Integrase strand-transfer inhibitors (INSTIs) constitute at present one of the pillars of first-line ART. Objectives: To study the prevalence of and the trend in transmitted drug resistance (TDR) to INSTIs in ART-naive patients in Spain. Methods: During the period 2012–17, 1109 patients from CoRIS were analysed. The Stanford algorithm v8.7 was used to evaluate TDR and transmission of clinically relevant resistance. To describe individual mutations/polymorphisms, the most recent IAS list (for INSTIs) and the 2009 WHO list update (for the backbone NRTIs used in combination with INSTIs in first-line treatment) were used. Results: Clinically relevant resistance to the INSTI class was 0.2%: T66I, 0.1%, resistance to elvitegravir and intermediate resistance to raltegravir; and G163K, 0.1%, intermediate resistance to raltegravir and elvitegravir. No clinical resistance to dolutegravir or bictegravir was observed. The prevalence of INSTI TDR following the IAS-USA INSTI mutation list was 2.6%, with no trend towards changes in the prevalence throughout the study period. The overall prevalence of NRTI WHO mutations was 4.3%, whereas clinically relevant resistance to tenofovir, abacavir and emtricitabine/lamivudine was 1.7%, 1.9% and 0.7%, respectively. Conclusions: Given the low prevalence of clinically relevant resistance to INSTIs and first-line NRTIs in Spain, it is very unlikely that a newly diagnosed patient will present with clinical resistance to a first-line INSTI-based regimen. These patients may not benefit from INSTI and NRTI baseline resistance testing.